The Influence of Media Exposure on Corruption on Anti-Corruption Disclosure in Sustainability Reports: A Study on State-Owned Enterprises Listed on the Indonesia Stock Exchange for the Period 2009–2023 - Luh Sri Diantari; Putu Agus Ardiana (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to examine the effect of media coverage on anti-corruption disclosure by State-Owned Enterprises (SOEs) listed on the Indonesia Stock Exchange (IDX) during the period 2009–2023. The research analyzes 195 sustainability reports published by listed SOEs in 2023. Content analysis is employed to assess the extent of anti-corruption disclosure, which serves as the dependent variable in this study. Media coverage is treated as the independent variable, while firm size, firm age, and industry classification are included as control variables. Legitimacy theory is used as the theoretical framework to explain the research findings. Multiple linear regression analysis is applied to test the hypotheses. The results indicate that media coverage has a highly significant positive effect on anti-corruption disclosure in the same year and a significant positive effect on disclosure in the following year. These findings suggest that media exposure encourages companies to respond to public pressure by enhancing transparency and accountability in addressing anti-corruption issues.